The Normativity of The Principle of Mutual Trust Between EU Member States within the Emerging European Criminal Area - Sulima, Aleksandra (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
The article deals with the issue of cooperation in criminal matters among European Union Member States. It analyses the emerging European Criminal Area, a form for cooperation aiming at establishing a single judicial area in criminal justice. The author describes the instruments and mechanisms of the ECA, which are unprecedented. However, this analysis is conducted from a unique perspective. Namely, the main issue explored in the paper is the principle of mutual trust. This principle, while recognised as a condicio sine qua non of deep cooperation, has not yet been fully implemented. The article presents explanations of both the theory and practice of mutual trust. It uses the jurisprudence of the European Court of Justice and the practice of the Member States to demonstrate the legal character of mutual trust within the emerging European Criminal Area. The paper emphasize the problematic issue of loopholes in EU primary and secondary law regarding mutual trust as the foundation of criminal cooperation. The author invokes many significant judgments of the Court of Justice, as well as declarations of EU institutions and Member States which highlight the importance of the respective principles. Thus, the law and jurisprudence, together with other non-binding documents, are compared and contrasted, revealing a certain paradox. In her conclusion the author shows the consequences of the determination of the normative character of mutual trust, threats facing it and future prospects for the realisation of the unique idea of a single area in criminal justice.
Keywords: Unia Europejska; współpraca w sprawach karnych; wymiar sprawiedliwości karnej; Europejski Trybunał Sprawiedliwości